Facilitating Consumer Learning in Insurance Markets: What Are the Welfare Effects?2. (25th March 2018) - Lagerlöf, Johan N. M.; Schottmüller, Christoph
Abstract: We model a monopoly insurance market in which consumers can learn their accident risks at a cost c . We then examine the welfare effects of a policy that reduces c . If c is sufficiently small ( c  <  c * ), the optimal contract is such that the consumer gathers information. For c  <  c *, both the insurer and the consumer benefit from a policy that reduces c further. For c   >   c *, marginally reducing c hurts the insurer and weakly benefits the consumer. Finally, a reduction in c that is successful, meaning that the consumer gathers information after the reduction but not before it, can hurt both parties.